Evaluation of sound level meter applications at control environment and quarry sites - Haoa, Daniel Tan Huan (Universiti Sains Malaysia, 2016)
Noise-induced hearing loss (NIHL), resulting from overexposure to loud sounds, is becoming increasingly prevalent among employees. Regulations established by the federal government recommend a maximum sound exposure level of 90 dBA for 8 hours, with an exchange rate of 5 dBA. Although sound level meters and dosimeters are accurate at measuring noise levels, they are expensive and inaccessible to common workers. Smartphones, on the other hand, are widely available to the average conswner and contain various downloadable sound level meter applications (SLM apps). SLM apps may be a more cost-effective solution to determining noise levels in various environments. This study examined the accuracy of four different free SLM apps on 3 different Android smartphones. Measurements of noise were taken at a controlled environment and four different sources at JKR Kuari Pusat Bukit Buloh. Results indicated that 2 SLM apps which are SPL Meter and iNVH in Lenovo model were the most accurate in determining noise levels in control environment (below 80 dBA) but inaccurate when applied at quarry site. Therefore, while SLM apps may be used on smartphones to help evaluate the noise conditions of a working environment, they may have limitations in their accuracy at higher level. Audiologists are advised to validate sound level